Some Relations Between Two Stages DNA Splicing Languages - Mudabera, Mohammad Hassan; Yuhani, Yusof; Mohd Sham, Mohamad (American Institute of Physics Inc., 2014)
A new symbolization of Yusof-Goode (Y-G) rule, which is associated with Y-G splicing system, was introduced by Yusof in 2012 under the framework of formal language theory. The purpose of this investigation is to present the biological process of DNA splicing in a translucent way. In this study, two stages splicing languages are introduced based on Y-G approach and some relations between stage one and stage two splicing languages are presented, given as theorems. Additionally, the existing relations between two stages splicing languages based on crossings and contexts of restriction enzymes factors with respect to two initial strings (having two cutting sites) and two rules are presented as subset.